Pengaruh Kebiasaan Membaca Surah Pendek Terhadap Pembentukan Kepribadian Religius Anak Di TK. Putri Kembar Kec. Sosa Julu - Febrina Rizky Hasibuan (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to determine the influence of the habit of reading short surahs on the formation of children's religious personalities at the PUTRI TEMBAR Kindergarten, Kec. Sosa Julu. This research uses quantitative methods. The population used in this research was 110 people, while the sample was taken 20% of the population, namely 22 people.This research uses a quantitative approach with an experimental type of research. The research design used pre-experimental with a one group pretest-posttest design type. The instruments used consist of observation, documentation and tests. The data analysis technique uses descriptive statistics and carries out conditional tests, namely the normality test and homogeneity test. Test the hypothesis using the "t" test. The population of this study were children at the PRINCESS KEMBAR kindergarten, sub-district. Sosa Julu District. Padang Lawas.The results of the research show that there is an increase in the religious personality of children in the PURI TEMBAR Kindergarten, Kec. Sosa Julu. This is proven by the results of pretest and posttest observations. The pretest observation results obtained an average of 59 and the posttest observation results were 77.99. The results of the hypothesis calculation obtained tcount = 1.681 by looking at t and the significance level a = 5% obtained ttable = 2.018 because tcount < ttable shows that there is a significant influence between the habit of reading short surahs on the formation of children's religious personalities in PRINCESS KEMBAR Kindergarten, Kec. Sosa Julu is proven from the results of calculating the value of tcount > ttable. H0 is rejected and Ha is accepted, so the conclusion is that there is an influence of the habit of reading short surahs on the formation of children's religious personalities in PRINCESS TWIN Kindergarten, Kec. Sosa Julu District. Padang Lawas.